A bibliometric analysis of diffuse large B-cell lymphoma research from 2001 to 2020. (July 2022) - Jiang, Junyi; Lyu, Wei; Chen, Na
Abstract: Diffuse large B-cell lymphoma (DLBCL) is a subtype of non-Hodgkin lymphoma (NHL) with the highest incidence, accounting for approximately one-third of NHL cases. Given the accumulated scientific publications related to the DLBCL domain, this study aimed to provide a comprehensive review of DLBCL studies from this millennium using the bibliometric method. With a strict retrieval strategy applied in the Web of Science database, a total of 10, 869 publications from 2001 to 2020 were obtained and exported. The temporal and geographical distribution of these publications and the performance of contributing countries, institutions, journals, and authors corresponding to these documents were investigated, as well as an in-depth content analysis through keyword co-occurrence. With regard to the most productive countries, the United States ranks first with 2344 (21.6%) publications and shows the most frequent collaborations with other countries. By contrast, China has demonstrated remarkable performance in the growth rate of publications over the years, and it ranks first in the number of publications in the last five years. The University of Texas System is the institution with the highest number of published articles (4.99%). Leukemia Lymphoma is the journal with the highest number of publications in this field which contributed 588 articles. Solid and close collaborations between scholars are becoming more frequent over the four five-year periods. Overall, the highest cooperation frequency in the last two decades happens to Gascoyne RD at the British Columbia Cancer Agency and British Columbia Cancer Research Center in Canada. By comparing the article citation and keyword co-occurrence in each five-year period, as well as the changes in keyword clusters over two decades, we conclude that the stage, evaluation, prognosis, and treatment of DLBCL have always been the research hotspots in this field. Meanwhile, the evolution of keyword co-occurrence over the years demonstrates that new clusters appear. For instance, the effect of ferroptosis mechanism in DLBCL, immunotherapy for DLBCL, and PDL-1, PDL-2, and CAR-T therapy have drawn increasing attention from academia. Our research highlights the key characteristics of DLBCL research and provides comprehensive insights into the research status and evolutions in this field. Highlights: The Diffuse large B-cell lymphoma (DLBCL) research trends are evaluated and the DLBCL knowledge structure are maped. The panorama of the DLBCL domain will help to accurately grasp the state-of-art and potential trends in future research. We expect to see more break throughs in immune metabolism and immunotherapy of DLBCL in the future.